The South African Flag Sign: An Electrocardiographic Flag for All Coronary Territories? - Steven Swarath MBBS; Nicole Maharaj MBBS; Andrew Hall MBBS; Jean Marie Frederick MBBS; Rajeev Seecheran MBBS, MHA; Valmiki Seecheran MBBS, MSc; Naveen Anand Seecheran MBBS (MD) (SAGE Publishing, 2023)
The South African flag sign (SAFS) is an acute, dynamic electrocardiographic (ECG) finding typically associated with first diagonal (D 1 ) artery occlusion. We report the case of a 47-year-old woman who exhibited this pattern but subsequently revealed the dreaded "widow-maker" lesion (100% occluded proximal left anterior descending [LAD] artery) and severe multivessel disease (90% stenosis of the posterior left ventricular [PLV] artery and 80% stenosis of the left circumflex artery [LCx]).